PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MOTOR HONDA DI CAPELLA BATAM - SW, Mislinda; Mardika, Nanda Harry (SCIENTIA JOURNAL, 2021)
This research aims to examine the influence of promotion and quality of service on the buying decision at the Capella Honda Batam Centre. This research uses a quantitative approach and nonprobability sampling techniques with a saturated sampling method. The data collection technique used a questionnaire with a Likert scale which was filled in by 242 respondents. Data were analyzed using SPSS version 25. The test results for the promotion variable were t count 4.426> t table 1.651 and sig t 0.000 <α 0.05. The result of quality of service variable test is t count 9.301> t table 1.651 and sig t 0.000 <α 0.05. The yield of the f test are f count 121.444> f table 3.033 and a significance of 0.000 <alpha 0.05, it can be concluded that promotion and quality of service partially and simultaneously have a significant effect on the buying decision at the Capella Honda Batam Centre. The test yield of the coefficient of determination have a value of 0.504, which means that 50.4% of variations in buying decision variables can be explained by promotion and quality service variables, the remaining 49.6% is explained by variables not examined in this study.